THE IMPACT OF UNEMPLOYMENT AND POVERTY ON ECONOMIC GROWTH IN THE CITY OF PALEMBANG - Utami, Tria; Riska, Nadia; Afifah, Ananda Putri; Firmansyah, Ferdi; Albar, Muhammad Dafa; Prasetyo, Muhammad Desviandra (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
In theory, economic growth has an influence on the level of poverty and unemployment. The data is used in the 2019 – 2021 time series. Poverty is indeed a very complex problem, because it also affects one factor, namely unemployment. When the unemployment rate increases, the poverty rate will automatically increase (Yacoub, 2012). The higher the poverty rate, the lower the education level. This is because poverty often leads to under-investment in education. Individuals living in poverty may not be able to access quality and adequate education. The city of Palembang is ranked first as the most populous in South Sumatra with a recorded population of 1,686,073 people, based on data from the Palembang Central Statistics Agency (BPS) for 2021. With this large number, it has a large impact on unemployment and poverty rates. South Sumatra itself is one of the provinces included in the top 10 poverty rates in Indonesia.